EKSISTENSI ILMU HUKUM DALAM TINJAUAN KAJIAN EPISTEMOLOGI FILSAFAT - Irwansyahlubis; M. Sidik (JURNAL CERDAS HUKUM, 2022)
Law science is one of the scientific studies whose position and existence are still questioned today. Not a few of the legal experts question the position of legal science as a coherent and fundamental scientific instrument in legal studies. The same question also comes from social scientists, they participate in providing criticism and questions about the existence and essence of legal science. Even so, the existence of legal science as a science is true. Law science itself has its own characteristics, legal science has different characteristics when compared to other sciences in general. Characteristics that become a sign in the science of law include, being normative, practical and prescriptive. Even so, the dynamics that occur in the existence of legal science are still so sticking out until now. So it is very relevant if this paper is presented in the form of a scientific study using a philosophy of science approach. In order to see how the actual existence of law science is, as well as what law science looks like. And the methodology used in this paper is to use literature review. And the theoretical use is to use the epistemology from the branch of philosophy of science